Robustness of serial clustering of extratropical cyclones to the choice of tracking method - Pinto, Joaquim G.; Ulbrich, Sven; Economou, Theodoros; Stephenson, David B.; Karremann, Melanie K.; Shaffrey, Len C. (Tellus A: Dynamic Meteorology and Oceanography, 2016)
Cyclone clusters are a frequent synoptic feature in the Euro-Atlantic area. Recent studies have 24 shown that serial clustering of cyclones generally occurs on both flanks and downstream 25 regions of the North Atlantic storm track, while cyclones tend to occur more regulary on the 26 eastern side of the North Atlantic basin near Newfoundland. This study explores the 27 sensitivity of serial clustering to the choice of cyclone tracking method using cyclone track 28 data from 15 methods derived from ERA-Interim data (1979-2010). Clustering is estimated by 29 the dispersion (ratio of variance to mean) of winter (DJF) cyclones passages near each grid 30 point over the Euro-Atlantic area. The mean number of cyclone counts and their variance are 31 compared between methods, revealing considerable differences, particularly for the latter. 32 Results show that all different tracking methods qualitatively capture similar large-scale 33 spatial patterns of underdispersion / overdispersion over the study region. The quantitative 34 differences can primarily be attributed to the differences in the variance of cyclone counts 35 between the methods. Nevertheless, overdispersion is statistically significant for almost all 36 methods over parts of the Eastern North Atlantic and Western Europe, and is therefore 37 considered as a robust feature. The influence of the North Atlantic Oscillation on cyclone 38 clustering displays a similar pattern for all tracking methods, with one maximum near Iceland 39 and another between the Azores and Iberia. The differences in variance between methods are 40 not related with different sensitivities to the NAO, which can account to over 50% of the 41 clustering in some regions. We conclude that the general features of underdispersion / 42 overdispersion of extra-tropical cyclones over the North Atlantic and Western Europe is 43 robust to the choice of tracking method. The same is true for the influence of the North 44 Atlantic Oscillation on cyclone dispersion.